Current status and development prospects of India’s pig industry - THOMAS, R; SINGH, V; GUPTA, V K (The Indian Journal of Animal Sciences, 2021)
Pig production and marketing have been driven by the growing consumer demand for high quality and low cost animal protein. As a result, organized and industrial piggery has been rapidly developing globally. For the Indian piggery sector, there exists a well-defined domestic market as well as an enormous market for international trade by stimulating its production activities. To meet the need for developing domestic as well as the international pig production and pork trade, this article describes the current status of the pig industry, its production in India and the factors that may affect its development. Production systems, quality of germplasm, urbanization, available farmland, grain production, water resources, bio-security issues and management practices encompass some of these factors. In addition, the effects of the culture and education of the populations on the development of pig sector in India are also discussed. Understanding the development of the pig production system and its associated factors is critical for assessing India’s impact and implication in the emerging international agricultural market.